Radical prostatectomy for clinically advanced (cT3) prostate cancer since the advent of prostate‐specific antigen testing: 15‐year outcome - Ward, John F.; Slezak, Jeffrey M.; Blute, Michael L.; Bergstralh, Erik J.; Zincke, Horst (BJU international, 2005)
In the first paper in this section, authors from the Mayo Clinic describe their experience and 15‐year outcomes in the controversial subject of radical prostatectomy in patients with clinical T3 prostate cancer. The findings were interesting in many respects, but the authors concluded that radical prostatectomy as part of multimodal treatment for patients with clinical T3 disease offers cancer control and good survival rates. There follows a series of papers on both prostate cancer and bladder cancer, but the final paper in this section from the UK attempts to define the accuracy of urologists and oncologists in assessing patient life‐expectancy. Using various methods they found that, rather disappointingly, doctors were poor at predicting 10‐year survival, leading to the possible outcome that some patients may be denied treatment after a pessimistic assessment of life‐expectancy. OBJECTIVE To report a long‐term experience with extirpative surgery in patients presenting with locally advanced (cT3) prostate cancer, as the best management of such patients remains a problem. PATIENTS AND METHODS In a single‐institution retrospective study identifying 5652 men who had radical prostatectomy (RP) for histologically confirmed prostate cancer since the advent of prostate‐specific antigen (PSA) testing (1987–97), 15% (842) had RP for cT3 disease. The median follow‐up of these men was 10.3 years. Cancer‐specific, overall and disease‐free survival was plotted and compared with those of patients having RP for cT2 disease during the same period. Perioperative morbidity, continence and erectile function rates were examined, with a multivariate analysis for risk factors of disease recurrence. RESULTS Freedom from local or systemic disease at 5, 10, and 15 years after RP for cT3 disease was 85%, 73% and 67%; the respective cancer‐specific survival rates were 95%, 90% and 79%. Significantly many men who did not receive neoadjuvant therapy (27%) were clinically over‐staged (pT2) and most men with pT3 disease (78%) received adjuvant therapy. The mean time to adjuvant therapy after RP was not significantly different between men with cT3 and cT2 disease (4.0 and 4.3 years). Pathological grade (≥7), positive surgical margins, and nondiploid chromatin were all independently associated with a significant risk for clinical disease recurrence, while preoperative PSA level had little effect on outcome. Complications and continence rates after RP in patients with cT3 mirrored those in patients with cT2 disease. CONCLUSIONS Significantly many patients with cT3 prostate cancer are overstaged (pT2) in the PSA era. RP as part of a multimodal treatment strategy for patients with cT3 disease offers cancer control and survival rates approaching those achieved for cT2 disease. Pathological grade, ploidy and margin status are all significant predictors of outcome after RP. Complications and incontinence rates in patients with cT3 disease mirror those after RP for cT2 disease.